2019
DOI: 10.1007/s00425-019-03178-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcript and metabolic adjustments triggered by drought in Ilex paraguariensis leaves

Abstract: Main conclusion Abscisic acid is involved in the drought response of Ilex paraguariensis. Acclimation includes root growth stimulation, stomatal closure, osmotic adjustment, photoprotection, and regulation of nonstructural carbohydrates and amino acid metabolisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…When analyzing the accumulation of dry weight by compartments, we observed that there were no differences in the accumulation of dry weight from roots, but there was a reduction for aboveground tissues of the yerba mate plants (leaves and stems) ( Figure 4A, 4B and 4C). Reduction in the accumulation of dry weight of leaves and stems was also observed in the clone "Garruchos 18" of I. paraguariensis, but in this case, the accumulation of dry weight of roots increased in stressed plants in relation to non-stressed plants (Acevedo et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…When analyzing the accumulation of dry weight by compartments, we observed that there were no differences in the accumulation of dry weight from roots, but there was a reduction for aboveground tissues of the yerba mate plants (leaves and stems) ( Figure 4A, 4B and 4C). Reduction in the accumulation of dry weight of leaves and stems was also observed in the clone "Garruchos 18" of I. paraguariensis, but in this case, the accumulation of dry weight of roots increased in stressed plants in relation to non-stressed plants (Acevedo et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…not show any visible virus-like symptoms [6]. The 390,909,798 2x101nt raw reads from the SRA were computationally analyzed according to Debat and Bejerman [7].…”
mentioning
confidence: 99%
“…The raw sequence data analyzed in this study correspond to an RNAseq library (SRA: SRP110129), associated with the National Center for Biotechnology Information (NCBI) Bioproject PRJNA375923. Data were obtained by Illumina Hiseq 1500 sequencing of total RNA isolated from yerba mate mature leaves collected in Gobernador Virasoro, Corrientes, Argentina (BioSample: SAMN07206716), that did not show any visible virus-like symptoms [6]. The 390,909,798 2×101nt raw reads from the SRA were computationally analyzed according to Debat and Bejerman [7].…”
Section: Figurementioning
confidence: 99%